(3HZjI GdLfGf aj YbGFO GdEjeGfs - (3LO Hf YHO Gddg Hf jMjis ((3ehQjJGfjG s)
(3ChdgG (B:s
(3GdMeO ddg GdPi YdefG JhjMOg deG Hg cdafG hNUfG ef aVdg Hef YQL Hg JcQekG dg s
(3BNQgG (B:s
(3Ydjg CRci GdUdhGJ hCJe eG Je EQSGd Hg heG NJe GfJgi Ydi jO cGJHg eMeO GdMGaX s
(3HgG fXGe GdJYbjHIs
(3efXheI ai GdJhMjOs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeYgO GdehQjJGfi ddHMK GdYdei (B((3JhMjO (B414) s
Keywords: (3GdJhMjO hGdedd hGdfMds